The Role of a Design-Thinking-Based Instructional Strategy in Promoting 21st Century Skills - Al-Amry, Naif Ali; Al-Abdul Al-Karim, Rashid Hussein (Journal of Curriculum and Teaching Methodology, 2024)
This research aimed to understand the role of a design-thinking-based instructional strategy in promoting 21st century skills targeted by the National Framework of Curricula Standers in Saudi Arabia. Considering the importance of the 21st century skills for learners; this research highlights the role of design thinking in promoting communication skills as one of the learning and innovation skills, known as the 4Cs: critical thinking, creative thinking, communication, and collaboration. A qualitative approach using basic interpretive study design was adapted to achieve the goal of this study. Data were gathered through observation, semi-structured open-ended interviews with the participant teacher and students, as well as through reflective questions answered by participating students. Findings from this research revealed that design thinking has a positive role in promoting communication skills for students by providing them communicative environment. These findings will contribute to the literature on design thinking in educational context and may have implications for educators.
Keywords: Design Thinking; The National Framework for General Education Curricula Standers in the Kingdom of Saudi Arabia; 21st century skills; Learning an Innovation Skills (4Cs); Communication